2019
DOI: 10.1186/s12931-019-1024-z
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell mobilisation and recruitment in pulmonary arteries in chronic obstructive pulmonary disease

Abstract: Background Pulmonary vascular abnormalities are a characteristic feature of chronic obstructive pulmonary disease (COPD). Cigarette smoking is the most important risk factor for COPD. It is believed that its constant exposure triggers endothelial cell damage and vascular remodelling. Under pathological conditions, progenitor cells (PCs) are mobilized from the bone marrow and recruited to sites of vascular injury. The aim of the study was to investigate whether in COPD the number of circulating PCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the pulmonary arterial wall of patients with COPD, an increase in the number of CD45 + cells has been observed, along with a decrease in the number of circulating progenitor cells. These changes were associated with endothelial dysfunction and vessel remodeling ( 146 ). In the adventitial layer, total leukocytes increase, especially CD8 + T cells, albeit with no changes in neutrophil or macrophage numbers.…”
Section: Pulmonary Vascular Remodeling In Chronic Lung Diseasesmentioning
confidence: 99%
“…In the pulmonary arterial wall of patients with COPD, an increase in the number of CD45 + cells has been observed, along with a decrease in the number of circulating progenitor cells. These changes were associated with endothelial dysfunction and vessel remodeling ( 146 ). In the adventitial layer, total leukocytes increase, especially CD8 + T cells, albeit with no changes in neutrophil or macrophage numbers.…”
Section: Pulmonary Vascular Remodeling In Chronic Lung Diseasesmentioning
confidence: 99%
“…The lack of appropriate epithelialization rate and disruption of the mucociliary system cause microbial overload and vulnerability to viral infection. Endothelial layer damage and aberrant vascular remodeling reduce the number of recruited circulating stem cells into the pulmonary niche, resulting in local stem cell exhaustion, cellular senescence, and reduced regeneration capacity [81][82][83].…”
Section: Post-covid Complications In Patients With Background Copd An...mentioning
confidence: 99%
“…Intratracheal application of bone marrow-derived EPCs attenuated the development of pulmonary emphysema in mice exposed to CS in a long term murine study, via the alleviation of inflammatory infiltration, decreased proteolytic enzyme activity, and improved antioxidant activity (298). In contrast, enhanced progenitor cell numbers in pulmonary arteries obtained from patients with COPD were associated with decreased endothelium-dependent dilation and inversely correlated with arterial lumen area (299). However, the characterization of these cells by progenitor marker expression was limited in this study.…”
Section: Stem Cells and Vascular Regeneration In Copd/emphysemamentioning
confidence: 99%
“…However, the characterization of these cells by progenitor marker expression was limited in this study. As the level of circulating EPCs is decreased but their migratory potential and adhesion is increased in COPD, it was suggested that circulating ECs are recruited to pulmonary tissue in COPD (296,299,300). This might not be beneficial in COPD patients, since circulating progenitor cells in these patients show impaired angiogenic ability, increased apoptosis, and impaired NO production compared with these features of EPCs obtained from healthy, non-smoking controls (301,302).…”
Section: Stem Cells and Vascular Regeneration In Copd/emphysemamentioning
confidence: 99%